FRI0403 Mesangial Proliferative Lupus Nephritis (ISN/RPS CLASS II): Clinical and Prognosis in A Cohort of 45 Patients. (10th June 2014) - Albert, G.; Narváez, J.; Ricse, M.; Estrada, P.; Zacarías, A.; Pestaña, M.; Mora, C.; Rozadilla, A.; Fulladosa, X.; Nolla, J.M.; Rubio Rivas, M.
Abstract : Background: Mesangial proliferative lupus nephritis (MPLN) or class II has traditionally been considered a mild form of nephritis, with good response to corticosteroid treatment. However, recently some studies have been published that observe high rates of recurrence and histological progression class. Objectives: To analyze the clinical presentation and the evolutive course of a cohort of patients with mensangial proliferative lupus nephritis. Methods: Two hundred forty-three SLE patients were studied. They were attended between 1980 and 2013 in a tertiary university hospital, without pediatric population, and registered in a specific database (AQUILES database). MPLN patients confirmed by renal biopsy (criteria ISN/RPS) were selected for analysis. In the evaluation of the response, we considered "responders" the patients who achieved remission (partial or complete) after completing induction therapy. The state of "non-responder" included non-response (absence of complete or partial response of renal disease after completing induction therapy), progression of class or death due to lupus nephritis. Results: We identified 45 patients (36 women) with a mean age (SD) at the time of diagnosis of nephritis 39.5 (12.3) years. The time evolution (median) from diagnosis of SLE to the development of nephritis was 33 months. We detected proteinuria higher than 0.5 gr/24 hours in 42 (93%) patients, hematuria in 31 (69%), granular casts in 1 (2%), mild renal insufficiency in 2 (4%), and hypocomplementemia in 22 (49%). The mean proteinuria was 1.62 (1.03) g/24 h. At the time of diagnosis or at follow-up 8 patients had nephrotic syndrome (17%), excluding in this record to those patients with nephrotic range proteinuria in the context of class progression. In the diagnostic biopsy, the mean activity index was 2.09 (1.6) and chronicity 0.5 (1.8). All patients were treated with prednisone (dose 0.5 to 1 mg/kg/day). Seventy-three percent (33/45) also had treatment with hydroxychloroquine. During evolution, in 16 patients (36%) was necessary to add immunosuppressive treatment for recurrences, unresponsiveness or progression of histological class, azathioprine was used in 13 patients (29%), mycophenolate in 7 (16%), cyclophosphamide on 2 (4%) and tacrolimus in 1 (2%). One year after treatment, 37 (83%) patients were considered "responders", of which, 30 patients (67%) were in complete remission and 7 (16%) in partial remission. In 6 of the 8 "non-responders", we observed a progression of the histology type in the second biopsy (class IV in 3 cases and class V in the other 3); one of these patients died at 6 months in the context of progression to class IV. Conclusions: In our cohort of lupus nephritis, the rate of non-responders achieved 17%. Studies are needed that allow us to identify which patients have worse prognosis and may well be candidates for more aggressive therapy to conventional steroid therapy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5317